Vaccination of Guinea Pigs with Nutritionally Impaired Avirulent Mutants of Mycobacterium bovis Protects against Tuberculosis - de Lisle, Geoffrey W. (American Society for Microbiology, 1999)
Four nutritionally impaired strains of Mycobacterium bovis produced by illegitimate recombination were tested for their ability to protect guinea pigs against intratracheal challenge with virulent M. bovis. All four strains and M. bovis BCG induced significant levels of protection as measured by the reduced spread of infection to the spleen and liver. In animals vaccinated with BCG or two of the other strains, the bacterial counts from the lungs were significantly lower than those of the nonvaccinated animals.